2021
DOI: 10.1080/09585192.2021.1914129
|View full text |Cite
|
Sign up to set email alerts
|

Controlled by the algorithm, coached by the crowd – how HRM activities take shape on digital work platforms in the gig economy

Abstract: effI), Innovation & entrepreneurship group, eBs universität für Wirtschaft und recht, oestrich-Winkel, germany; b centre for family entrepreneurship & ownership (cefeo), Business administration group, Jönköping International Business school, Jönköping, sweden; c Department of communication and culture, nordic centre for Internet and society, BI norwegian Business school, oslo, norway;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 74 publications
(203 reference statements)
0
37
0
Order By: Relevance
“…More research is needed to understand the mechanisms by which gig workers attain new skills and secure projects that allow them to develop professionally. For example, Waldkirch et al (2021) showed how gig workers are trained and developed by the crowd of more experienced workers on digital platforms. Less experienced workers are mentored, provided support and encouragement, and given advice on how to improve their self-presentation and identify profitable niches.…”
Section: Adapting To Gig Work: Implications For Organizations and For...mentioning
confidence: 99%
“…More research is needed to understand the mechanisms by which gig workers attain new skills and secure projects that allow them to develop professionally. For example, Waldkirch et al (2021) showed how gig workers are trained and developed by the crowd of more experienced workers on digital platforms. Less experienced workers are mentored, provided support and encouragement, and given advice on how to improve their self-presentation and identify profitable niches.…”
Section: Adapting To Gig Work: Implications For Organizations and For...mentioning
confidence: 99%
“…The HR architecture predicts that workers inside the organization's boundaries are core workers, and therefore subject to the HRM principles of the firm (Bowen & Ostroff, 2004;Lepak & Snell, 1999) Monitoring compliance with requesters' needs is core to HRM in OLPs. Gig workers in crowdwork platforms like Upwork and Fiverr are tightly controlled through algorithm-based appraisal systems (Sutherland et al, 2020;Wood et al, 2019b) and are subject to electronic surveillance (e.g., using screenshots) (Waldkirch et al, 2021).…”
Section: Olps Use Hybrid Hrm Systems To Manage Gig Workersmentioning
confidence: 99%
“…Monitoring compliance with requesters' needs is core to HRM in OLPs. Gig workers in crowdwork platforms like Upwork and Fiverr are tightly controlled through algorithm‐based appraisal systems (Sutherland et al, 2020; Wood et al, 2019b) and are subject to electronic surveillance (e.g., using screenshots) (Waldkirch et al, 2021). OLPs also use compliance‐based pay practices like piece‐based pay, and appraisal against strict pre‐set standards (e.g., degree to which a meal deliverer works during peak hours; Meijerink, Keegan, & Bondarouk, 2021; Veen et al, 2020).…”
Section: Realigning the Hr Architecture To Account For Olpsmentioning
confidence: 99%
“…Access to information and the ability to use information technology effectively has also been linked to venture success by helping connect entrepreneurs to needed resources and networks (Audretsch & Belitski, 2017 ). Online platforms can offer a range of options — entrepreneurs on online crowdfunding platforms (e.g., Kickstarter, Kiva) and marketplaces (e.g., Etsy) need to learn to effectively navigate the platform to their advantage and attract potential customers and investors (Allison et al, 2015 ; Mollick, 2014 ; Waldkirch et al, 2021 ). Understanding how to explain their businesses and describe the help they need effectively in an online setting may seem like a staggering task for an overburdened entrepreneur.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, we recognize that some of the factors hindering entrepreneurs from connecting with mentors may relate to entrepreneurs being overwhelmed by the platform, and not expecting to make a successful connection. The issue of "platform literacy" -learning to navigate the platform (Waldkirch et al, 2021(Waldkirch et al, , p.2659) is critical to finding success in a range of digital settings. Navigating networks effectively enables entrepreneurs to not only access relevant resources, but also provides them with the knowledge to use these resources effectively (Belitski and Büyükbalci, 2021;Elfring & Hulsink, 2003;Srećković, 2018).…”
Section: Verbal Persuasion To Help Entrepreneurs Use the Platformmentioning
confidence: 99%